2010
DOI: 10.4236/jmmce.2010.93016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Fly Ash Filled High Density Polyethylene

Abstract: Effect of fly ash as filler in mechanical properties of HDPE is described in this study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 7 publications
4
35
1
2
Order By: Relevance
“…This shows that increase in FA may lead to increase in flexural modulus while increase in CC may lead to a decrease in flexural modulus. This is in line with the work of Ahmad and Mahanwar [24] who reported that increase in FA content leads to increase in flexural modulus. Gummadi et al [3] …”
Section: Differential Scanning Calorimetrysupporting
confidence: 81%
See 1 more Smart Citation
“…This shows that increase in FA may lead to increase in flexural modulus while increase in CC may lead to a decrease in flexural modulus. This is in line with the work of Ahmad and Mahanwar [24] who reported that increase in FA content leads to increase in flexural modulus. Gummadi et al [3] …”
Section: Differential Scanning Calorimetrysupporting
confidence: 81%
“…It is observed that flexural strength decrease initially when the combination of the filler is dominated by CC but increase sharply when the filler content is dominated by FA. It has been reported that increase in the content of fly-ash to polyethylene leads to increase in flexural strength [24]. The authors attributed this increase to the formation of fairly strong interfacial bond between the matrix and filler leading to an effective stress transfer from matrix to filler.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 97%
“…In addition, coal has natural antifungal properties and low water absorption capacity (compared to wood). While coal combustion byproducts such as fly ash and cenospheres have been evaluated as fillers for plastic composites , only recent research efforts have begun to explore the possibility of using coal as a filler in thermoplastic and thermosetting polymers. Hu et al incorporated coal with sodium humate coupling agent into a mixture of carboxymethyl starch and polyvinyl alcohol to increase the tensile strength of thin plastic composite films to approximately 10 MPa with 60 weight percentage (wt%) coal.…”
Section: Introductionmentioning
confidence: 99%
“…It has wide applications in structural, packaging, and other commercial products. Reinforcement of HDPE with FA particles has led to the significant improvement in different properties of HDPE, for example, Ahmad and Mahanwar studied mechanical properties of FA (containing three different particle sizes) reinforced HDPE composites and observed an increase in tensile and flexural strengths and moduli with reduction in elongation at break for particles with smallest size. Satapathy et al .…”
Section: Introductionmentioning
confidence: 99%